The dramatic song how songs tell stories in Filipino television drama series - Bordador, Ma. Jocelyn C.
"This thesis deals primarily with the question of correlation between an original Filipino television drama and its theme song. The researcher of this thesis has aimed to prove if the content of an original Filipino television drama or teleserye can define and affect the piece of music that is used as its theme song. This study also tries to prove that a teleserye theme song can actively disseminate messages and reinforce emotions and values found and perpetuated in Filipino television program formats, in this case, the drama format. This thesis has also sought to present, to a certain extent, how the teleserye and teleserye theme song could affect the teleserye-viewing audience. To prove these assumptions, the researcher first isolated certain variables which she deemed as common values and traits prevalent in Filipino television dramas such as love, desire, courage and power. The researcher then tabulated the frequency and consistency of each one in both the teleserye she chose and their corresponding theme songs through the use of the content analysis method. In order to evaluate if her analyses were congruent with the original plans of the creative and production teams of each teleserye, she interviewed the directors, scriptwriters and songwriters of each one and asked them whether or not they intentionally unified the content of the theme songs with the contents of the teleserye. Finally, the researcher conducted focus group discussions in order to assess if the audience of these teleserye literally and figuratively saw, heard and felt the messages and emotions discovered by the researcher and validated by the production teams behind these teleserye. Upon closer analysis, it was revealed to the researcher that a teleserye theme song would play up only one aspect of the complex storyline of a teleserye, usually the romantic or love-related aspects of it. Although the trend in teleserye at the time they were shown and studied by this researcher was to lean heavily towards the fantastic and supernatural, and filial love (specifically the parent-child and sibling relationships) remained a constant infredient in teleserye plotlines, this researcher discovered that these elements were largely ignored in the theme songs she chose to analyze in favor of situations found in real life, outside the world of the teleserye. This researcher also realized through the course of her analysis that some songs revealed more important plot points than others, such as the quest through different worlds in Panday through the lyrics of its theme song Makita Kang Muli, and the plea of children to find love in the teleserye Mga Anghel na Walang Langit along with its titular theme song. Through the interviews the researcher conducted with the creative and production team of each teleserye, and to a lesser degree scriptwriting for teleserye themselves, was reinforced. This was alo concurred by the audience of these teleserye, who she was able to tal through the focus group discussions she conducted. This thesis has reached the conclusion that the content of an original Filipino television drama or teleserye influences the creation and execution of its theme song. There may be instances where the teleserye theme song may not be deeply rooted to the teleserye it was made for, however certain aspects of the teleserye may be played up in the theme song. Nonetheless, it is paramount that the teleserye has a unique plotline that appeals to the interests or sentiments of the audience regardless of whether or not its theme song bears the same uniqueness, storytelling elements, or appeal."